PENGEMBANGAN MEDIA PEMBELAJARAN SENI BUDAYA DI SEKOLAH DASAR BERBASIS MIT APP INVENTOR PROFESSIONAL DALAM TEAM BASED PROJECT PROTOTYPE CURRICULUM - Putra Afriadi; Naeklan Simbolon; Fahrur Rozi (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2022)
This study aims to design and develop Fine Arts Learning Media Using Professional MIT App Inventors in a Team Based Project-Based Prototype Curriculum for PGSD FIP UNIMED students. The use of applications is certainly an alternative to fulfill students` artistic competence as prospective teachers. The context of students who come from cultural diversity is the basis for researchers to create teaching materials that can include various arts and cultures in Indonesia. The product results have gone through the stages of validity, implementation and effectiveness testing. With trials conducted, the resulting product is valid (proper in content and appearance), implementation (easy to use by lecturers and students), and effective (can improve student learning processes and outcomes). The development model uses a 4D model that emphasizes the need for learning outcomes. In the identification phase, needs analysis, concept analysis, technical training success analysis, usage analysis and cultural diversity analysis are conducted. The development phase is implemented with 3 main activities: validation testing, implementation testing, and performance testing. At the last stage, the product is widely distributed.